Ultrasound-Guided vs. Landmark-Guided Lumbar Puncture for Obese Patients in Emergency Department - Li, Lei; Tao, Weichen; Cai, Xue (Frontiers in Surgery, 2022)
Objective: Emergency patients are in severe and urgent condition. If the patient is obese, the traditional lumbar puncture method is more difficult. This study was to observe the comparison of ultrasound-guided and landmark-guided lumbar puncture for obese patients in the emergency department. Methods: Sixty patients suspected of intracranial infection, subarachnoid hemorrhage, and intraventricular hemorrhage from January 2018 to June 2020 were selected in the Department of Emergency Medicine, Shengjing Hospital of China Medical University. They were randomly assigned to 2 groups according to the order of enrollment: Group A (Landmark-guided group, n=30) and Group B (Ultrasound-guided group, n=30). Follow-up assessments were performed to observe lumbar puncture time, the number of bloody CSF, Visual Analogue Scale (VAS), the complications, and satisfaction. Results: Compared with group A, group B had less lumbar puncture time, lower puncture attempts, and a higher first puncture success rate (P<0.05). In group B, the number of bloody CSF was less (P<0.05), postprocedural low back pain was less (P<0.05), intraprocedural sciatic nerve irritation and postprocedural paresthesia were less, but the difference was not statistically significant (P>0.05). Compared with group A, the postprocedural VAS in group B was lower, and the difference was statistically significant (P<0.05). The total satisfaction of group A and group B was 60.0% and 86.7%, respectively. The total satisfaction of group B was higher than that of group A (P<0.05). Discussion: Ultrasound-guided lumbar puncture can be used for obese patients with difficulty in the lumbar puncture. It is worthy of clinical application and promotion.